General Anesthesia in Day-Case Surgery by Laryngeal Mask Airway - Hassan, Md Kamrul; Aziz, Mohammad Abdul (IAHS Medical Journal, 2025)
Background: In the recent few years some unwanted catastrophic complications developed in day-case surgery due to uneven airway management. Most of them fail to maintain proper airways. Laryngeal Mask Airway (LMA) provides a reliable airway during general anesthesia without serious complications and in some cases may not need muscle relaxants for insertion and may thus be considered a suitable alternative for tracheal tubes. The difficult airway is a nightmare situation for anesthesiologists and the scenario has changed with the introduction of LMA. To assess the outcome of General Anesthesia in day-case surgery by LMA (Laryngeal Mask Airway) this study was done. Materials and methods: 150 patients were randomly selected for day case surgery in Institute of Applied Health and Sciences (IAHS) Hospital and Chevron Eye Hospital and Research Center, Chattogram during the period April 2018 to May 2024. The number of attempts and time taken for successful placement to achieve effective ventilation were recorded. Hemodynamic parameters, quality of recovery score and ventilation (Regarding the audible leak, chest movement, tidal volume loss, requirement of manipulation) and complications were recorded. Results: 150 patients were selected for the study. It was observed that LMA could be successfully placed in the first attempt in 83.33% and 2nd attempt in 15.3% cases. Failed insertion was recorded in 1.3% cases due to the inappropriate size of LMA and the deformity of the patient's face. The overall time of insertion of LMA was within 20 to 25 seconds in 93% of cases and 25 to 30 seconds in 2nd attempt to compare of quality of ventilation in terms of audible air leak over the mouth after achieving a cuff pressure of 60 cm of H2O with the recommended volume of air. It was found that the audible leak was found in some cases which was corrected by a little more pressure from the recommended pressure. Qualities of ventilation in terms of chest movement were found good in most of the cases, 96% were statistically insignificant. Tidal volume loss was found in only a few patients which was found due to lower inspiration pressure. The sore throat was found in 5 cases , Gastric insufflation was noted in 4 cases, regurgitation in 1 case. Hoarseness was not found in this study. Conclusion: After considering satisfactory first-attempt insertion success rate, easy diagnosis of misplacement, less hemodynamic changes, better quality of ventilation and less postoperative morbidity, it can be concluded that LMA is a better option for airway management in day-case surgery. IAHS Medical Journal Vol 7(2), December 2024; 52-57